Possibility of Benefiting from Malaysia's Experience in Stimulating the Private Sector ‎Through Financing Methods in Iraq - Abbas, Shiama; Sabah Nema Ali , Sabah Nema Ali (Journal of Economics and Administrative Sciences, 2025)
This research investigates the possibility of assessing and applying Malaysia's learning-information-base of successful private sector financing strategies for spurring economic growth in the Iraqi setting. The Malaysian model, especially with regard to support for small and medium enterprises (SMEs), is studied to chart the relevance and applicability of the concept to the Iraqi economy in the span of 2004-2023. Adopting descriptive-analytical and inductive method, the study brings forth Malaysia's diversified financing arrangements involving internal sources, external sources, public-private partnerships, and incentives with a specific aim. It is found that the Malaysian systems for its SME development, along with tax incentives and strategic privatization, contributed enormously to GDP growth and job creation, whilst on the contrary, the Iraqi economy remains strongly oil-dependent, with some meager participation of the private sector, mostly due to bad financing structures and policy inefficiencies. Three strategic scenarios are suggested to Iraq: improving the business environment; SME development; and public-private partnerships. If implemented, these strategies will make Iraq's economy more resilient, reduce unemployment rate, and provide more sources of revenues.